On the Convex Parameterization of Constrained Spacecraft Reorientation - Yoonsoo Kim; Mesbahi, M; Singh, G; Hadaegh, F Y (IEEE transactions on aerospace and electronic systems, 2010)
Guiding the rotational motion of a spacecraft subject to constraints on its permissible orientation often leads to nonconvex optimal control problems. In this paper, we consider convex parameterizations of sets associated with the constrained rigid body orientations. We then elaborate on ramifications of such a parameterization in the development of steering laws for autonomous spacecraft reorientation that are based on convex optimization algorithms. Such problems appear in almost every space science mission equipped with heat- or light-sensitive instruments, e.g., cryogenically cooled infrared telescopes, star trackers, and low-energy ion composition analyzers. An example, demonstrating the viability of the proposed algorithm for constrained multiple spacecraft reorientations concludes the work presented here.